2018
DOI: 10.1080/10942912.2018.1466319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chitosan and oregano extract on the physicochemical properties of microencapsulated fish oil stored at different temperature

Abstract: Fish oil is an excellent source of omega-3 fatty acids and is easily susceptible to oxidation. Microencapsulation is a commonly employed technique to protect fish oil against oxidation. In the present study, the potential of chitosan in combination with bovine gelatin and maltodextrin as wall material for microencapsulation of fish oil by spray drying was evaluated. To improve the oxidative stability of the fish oil microencapsulates, oregano (Origanum vulgare L) extract was added at 0.50 g/100 g of emulsion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…However, the effect was more pronounced in the MD21-based microcapsules (PV = 9.01 ± 0.13 meq O2/kg oil after six weeks storage at 25 °C). This positive correlation between the lipid oxidation rate and storage temperature on microencapsulated fish oil has also been reported by other authors [33,34] and could be attributed to the loss of natural antioxidants, as well as an increase in diffusivity of the prooxidant agents (e.g., oxygen, radicals and trace of metals) at higher temperatures. Moreover, it is noteworthy that the PV results of this study were lower than others reported in literature that also produced fish oil microencapsulates within carbohydrate matrices.…”
Section: Oxidative Stability Of the Microencapsulatessupporting
confidence: 87%
“…However, the effect was more pronounced in the MD21-based microcapsules (PV = 9.01 ± 0.13 meq O2/kg oil after six weeks storage at 25 °C). This positive correlation between the lipid oxidation rate and storage temperature on microencapsulated fish oil has also been reported by other authors [33,34] and could be attributed to the loss of natural antioxidants, as well as an increase in diffusivity of the prooxidant agents (e.g., oxygen, radicals and trace of metals) at higher temperatures. Moreover, it is noteworthy that the PV results of this study were lower than others reported in literature that also produced fish oil microencapsulates within carbohydrate matrices.…”
Section: Oxidative Stability Of the Microencapsulatessupporting
confidence: 87%
“…Natural extracts are a widely investigated class of natural products, often implemented for the formation of chitosan particles. Over the past five years, several research teams have presented the synthesis of chitosan micro- or nano-particles loaded with a plethora of extracts, such as Centella asiatica [ 122 ], Cinnamomum cassia [ 123 ], Plinia cauliflora (jabuticaba) fruit peel [ 124 ], Origanum vulgare L [ 125 ], Mentha longifolia [ 126 ], Physalis alkekengi -L [ 127 ], Eugenia dysenterica [ 128 ] or grape and apple pomace phenolic extract [ 129 ], aiming at their enhanced characteristics in order to be applied in various fields.…”
Section: Chitosan As a Matrix For Nanosystemspreparation: Methodsmentioning
confidence: 99%
“…The clove extract and eugenol acetate showed an antioxidant effect in cod liver oil comparable to that of α‐tocopherols (Lee & Shibamoto, 2001). In other studies (Annamalai et al, 2015; Jeyakumari et al, 2018), ginger essential oil and oregano extract were found to improve the oxidative stability of microencapsulated fish oil. Bhale et al (2007) found methanol extracts of rosemary and oregano to reduce fish oil omega‐3 acid degradation during accelerated oxidation.…”
Section: Polyphenols As Antioxidants In Fish Oilsmentioning
confidence: 77%